Frequency of Metabolic Syndrome on Diabetes Mellitus Patients in Surabaya - Dyah Peni Puspitasari; Budi Widodo; Jongky Hendro Prayitno (Biomolecular and Health Science Journal, 2018)
Introduction: Metabolic syndrome is a syndrome characterized by central obesity, high blood glucose or impaired glucose tolerance, dyslipidemia, and high blood pressure. Nearly 70% to 80% of Diabetes melitus (DM) population was diagnosed with metabolic syndrome. We aimed to present the data of frequency of metabolic syndrome in patients with DM for a basis of future research.Methods: This is a descriptive study design on DM patients based on NCEP ATP III criteria. The data was collected from direct measurements and laboratory results of all DM patients: waist circumference, weight, height, and blood pressure of the subjects, triglyceride status (TG), high-density lipoprotein cholesterol (HDL-C) status, and fasting blood glucose status.Results: From 77 DM patients, results were obtained in this study were 69 (89.61%) patients with DM-metabolic syndrome  (DM-MetS) and 8 (10.39%) patients with DM-non-metabolic syndrome. From 69 patients with DM-MetS, 52 (75.36%) were female and 17 (24.64%) were male.Conclusion: A total of 69 (89.61%) patients with T2DM were diagnosed as metabolic syndrome.